Distinction of mouse interferon-alpha subtypes by polymerase chain reaction utilizing consensus primers and type-specific oligonucleotide probes - Hughes, Jr, T K; Chin, R; Tyring, S K; Rady, P L (Journal of interferon research, 1994)
We have developed a novel method to study the subtype-specific expression of interferon-alpha (IFN-alpha) in the mouse system: we synthesized and used consensus oligonucleotide primers to allow simultaneous polymerase chain reaction (PCR) amplification of multiple murine IFN-alpha gene sequences. In addition, a set of subtype-specific oligomer probes were designed and used to distinguish between IFN-alpha genes that differ by only a few bases. The consensus primers, corresponding to two regions highly conserved among murine IFN-alpha subtypes, were used in reverse transcription and PCR amplification of total cellular RNA, isolated from IFN-gamma-treated murine L-929 cells, to yield a fragment of the anticipated approximately 520-bp size. Southern analysis of the amplified product using an internal consensus oligomer probe confirmed specific amplification of murine IFN-alpha gene(s). Subtype-specific oligonucleotide probes indicate that IFNs-alpha 1, -alpha 2, and -alpha 5 are present following IFN-gamma treatment, whereas IFN-alpha 4 remains virtually absent. Our results indicate that the expression of specific IFN-alpha subtypes may be subject to complex regulation, dependent upon inducing agents and cell types involved, and countless other factors. The procedure described here represents a novel method for studying the subtleties of the murine IFN-alpha mRNA expression.